Pebandingan Implementasi E-Government Di Indonesia Dengan Singapura (Studi Kasus Pelaksanaan E-Government) - Wau, Miya Monika; Dompak, Timbul (LPPM Universitas Putera Batam, 2024)
This article's goal is to contrast Singapore's and Indonesia's approaches to e-government adoption. Comparing e-Government destinations' web designs is the goal of this study. Singapore has a website (www.gov.sg), while Indonesia has a website (www.Indonesia.go.id). The work area thinking and information collecting approach will be used to acquire this data. delivering data to the library so it may be transformed into research materials. The study's conclusion is that, in the present age of the industrial revolution, government operations will be significantly impacted by the implementation of e-Government. Every government implements things differently. a technique made possible by developments in ICT (information and communication technology). The process of implementing e-Government in Indonesia and Singapore is done by implementing e-Government in each nation separately. corresponding areas, both in terms of managing government operations internally and disseminating information to the general public.